Telehealth readiness in nursing practice: a walker and avant concept analysis - Aini Inayati; Sriyati Sriyati (UPPM STIKES Pemkab Jombang, 2026)
Abstract The rapid integration of telehealth into healthcare systems has transformed the delivery of nursing care, necessitating a clear understanding of the concept of telehealth readiness among nurses. Despite its growing significance, telehealth readiness lacks a uniform conceptual definition, creating ambiguity in research, education, and practice. This article aims to analyze and clarify the concept of telehealth readiness in nursing practice using Walker and Avant's concept analysis method. Walker and Avant's eight-step framework was employed to analyze telehealth readiness. A systematic literature review was conducted using databases including PubMed, CINAHL, Scopus, and Google Scholar, covering publications from 2015 to 2024. Three defining attributes were identified: (1) technological competency and digital literacy; (2) attitudinal readiness and professional confidence; and (3) organizational and infrastructural support. Antecedents include prior technology exposure, institutional training programs, and leadership support. Consequences encompass improved care quality, enhanced patient satisfaction, and increased professional efficacy. A refined conceptual definition of telehealth readiness in nursing is proposed. Implications for nursing education, clinical practice, and health policy are discussed.